Quantized Collision/Fusion Events of Anionic Ionosomes at a Polarized Soft Micro-Interface - Zhang Jingcheng; Huang Linhan; Fang Taoxiong; Xiang Zhipeng; He Sijia; Peljo Pekka; Gan Shiyu; Huang Xinjian; Deng Haiqiang (Wiley, 2025)
With single-entity collisional electrochemistry, anionic ionosomes (i. e., negatively-charged nanoscopic water clusters wrapped by an ionic bilayer) are quantitatively analysed at a positively polarized micro-water/oil interface. When Cl−-ionosomes in the organic phase collide/fuse with the polarized interface formed at the very tip of a micropipette, chloride ions will be released from an ionosome into the water phase manifested as a current spike along the timeline. Fusion mechanism along with sizing of ionosomes are readily uncovered via detailed analysis of the current spikes.